Do visual and step height factors cause imbalance during bipedal and unipedal stances? A plantar pressure perspective - Guo, Panjing; Wang, Duoduo; Li, Yumin; Wang, Ruiqin; Xu, Haoran; Han, Jia; Lyu, Jie (Frontiers in Bioengineering and Biotechnology, 2023)
Objective: The plantar pressure analysis technique was used to explore the static balance ability and stability of healthy adult males under the influence of visual and step height factors during bipedal and unipedal stances. Methods: Thirty healthy adult males volunteered for the study. Experiments used the F-scan plantar pressure analysis insoles to carry out with eyes open (EO) and eyes closed (EC) at four different step heights. The plantar pressure data were recorded for 10 seconds and pre-processed to derive kinematic and dynamic parameters. Results: For unipedal stance, most of kinematic parameters of the subjects’ right and left feet were significantly greater when the eyes were closed compared to the EO condition and increased with step height. The differences in toe load between right and left feet, open and closed eyes were extremely statistically significant (P < 0.001). The differences in midfoot load between the EO and EC conditions were statistically significant (P = 0.024) and extremely statistically significant between the right and left feet (P < 0.001). The difference in rearfoot load between EO and EC conditions was extremely statistically significant (P < 0.001) and statistically significant (P = 0.002) between the right and left feet. For bipedal stance, most of kinematic parameters of the subjects’ EO and EC conditions were statistically significant between the right and left feet and increased with step height. The overall load’s difference between EO and EC states was statistically significant (P = 0.003) for both feet. The overall load’s difference between the right and left feet was extremely statistically significant (P<0.001) in the EC state. The differences between the right and left feet of the forefoot and rearfoot load with EO and EC suggested that the right foot had a smaller forefoot load, but a larger rearfoot load than the left foot (P<0.001). The differences between the forefoot and rearfoot load of the subjects’ both feet with EO and EC were extremely statistically significant (P < 0.001). Conclusion: Both visual input and step height factors, even the dominant foot, act on kinematic and dynamic parameters that affect the maintenance of static balance ability.